Pemulihan Kesadaran pada Lingkungan Melalui Pemanfaatan Sosial Media (Lembaga Pengembangan Kinerja Dosen, 2025)
Waste management is a major environmental problem in Indonesia. The presence of social media provides the public with more opportunities to raise awareness of this issue. This study aims to explore the role of the Sungai Watch account in the waste cleanup program and how it affects the recovery of environmental awareness. This study uses a qualitative analysis method, involving a case study of Sungai Watch's activities and interactions on its social media accounts. The results show that Sungai Watch's effective use of social media increases community participation and raises public awareness of the importance of maintaining a clean environment. Waste cleanup programs promoted through social media can change community behavior in the short term and build the foundation for greater change in the long term.